Industrial gas turbine performance: Compressor fouling and on-line washing - Igie, Uyioghosa; Pilidis, Pericles; Fouflias, Dimitrios; Ramsden, Kenneth; Laskaridis, Panagiotis (ASME, 2014)
Industrial gas turbines are susceptible to compressor fouling, which is the deposition and accretion of airborne particles or contaminants on the compressor blades. This paper demonstrates the blade aerodynamic effects of fouling through experimental compressor cascade tests and the accompanied engine performance degradation using turbomatch, an in-house gas turbine performance software. Similarly, on-line compressor washing is implemented taking into account typical operating conditions comparable with industry high pressure washing. The fouling study shows the changes in the individual stage maps of the compressor in this condition, the impact of degradation during part-load, influence of control variables, and the identification of key parameters to ascertain fouling levels. Applying demineralized water for 10 min, with a liquid-to-air ratio of 0.2%, the aerodynamic performance of the blade is shown to improve, however most of the cleaning effect occurred in the first 5 min. The most effectively washed part of the blade was the pressure side, in which most of the particles deposited during the accelerated fouling. The simulation of fouled and washed engine conditions indicates 30% recovery of the lost power due to washing.
Keywords: compressor fouling; online washing; cascade blade aerodynamics and gas turbine performance simulation